1988
DOI: 10.1017/cbo9780511621024
|View full text |Cite
|
Sign up to set email alerts
|

Variation across Speech and Writing

Abstract: Similarities and differences between speech and writing have been the subject of innumerable studies, but until now there has been no attempt to provide a unified linguistic analysis of the whole range of spoken and written registers in English. In this widely acclaimed empirical study, Douglas Biber uses computational techniques to analyse the linguistic characteristics of twenty three spoken and written genres, enabling identification of the basic, underlying dimensions of variation in English. In Variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

74
2,516
4
198

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 3,456 publications
(2,792 citation statements)
references
References 0 publications
74
2,516
4
198
Order By: Relevance
“…"would", "should", "could"), and inverse scores of Articles ("a", "the") and Words of More Than Six Letters. These linguistic variables have been found to naturally co-occur in speech and writing, and to factoranalytically form one, usually the first, factor (Biber, 1988;Gill, et al, 2006;Pennebaker & King, 1999). All variables were standardized prior to their aggregation.…”
Section: Linguistic Analysis and Derived Measures Of Language Usementioning
confidence: 99%
See 1 more Smart Citation
“…"would", "should", "could"), and inverse scores of Articles ("a", "the") and Words of More Than Six Letters. These linguistic variables have been found to naturally co-occur in speech and writing, and to factoranalytically form one, usually the first, factor (Biber, 1988;Gill, et al, 2006;Pennebaker & King, 1999). All variables were standardized prior to their aggregation.…”
Section: Linguistic Analysis and Derived Measures Of Language Usementioning
confidence: 99%
“…private thoughts), (b) Neuroticism would be more strongly related to verbal emotional expression in participants' SOC than in their EAR-sampled language, and (c) verbal immediacy would be related to Extraversion in participants' EAR-sampled language and Neuroticism in their SOC language. Several studies across different labs have identified verbal immediacy as a core linguistic device that conveys a personal, involved, experiential language (Biber, 1988;Gill et al, 2006;Pennebaker & King, 1999). The last prediction, then, is based on the idea that verbal immediacy facilitates social processes in interpersonal contexts and emotional processes in private contexts (Wiener & Mehrabian, 1968).…”
mentioning
confidence: 99%
“…The difference between principal component analysis and cluster analysis, in short, is that while the former groups variables, the latter groups cases. In linguistics, principal component analysis has been applied in studies of register variation (for instance, Biber, 1988), corpus linguistics (for instance, Keune et al, 2005), and dialectology (for instance, Shackleton, 2005). As Shackleton (2005:142) succinctly puts it, ''applied to a data set of linguistic features, principal component analysis may isolate sets of linguistic features that tend to occur together and not with other features.''…”
Section: Dimensions Of Morphosyntactic Variance: Principal Component mentioning
confidence: 99%
“…Four additional features are based on word lists developed by Biber and his colleagues. These include the frequency per thousand words of academic verbs, abstract nouns, topical adjectives, and cognitive process nouns (see Biber, 1986Biber, , 1988Biber, Johansson, Leech, Conrad, & Finegan, 1999;Biber et al, 2004). Two measures of word length are also included: average word length measured in syllables and the frequency per thousand words of words containing more than eight characters.…”
Section: Component 1: Academic Vocabularymentioning
confidence: 99%